Multifaceted Role of Probiotics in Enhancing Health and Growth of Aquatic Animals: Mechanisms, Benefits, and Applications in Sustainable Aquaculture—A Review and Bibliometric Analysis - null Madhulika; Soibam Ngasotter; Maibam Malemngamba Meitei; Tao Kara; Martina Meinam; Sanjeev Sharma; Sanjaykumar Karsanbhai Rathod; Sanjenbam Bidyasagar Singh; Soibam Khogen Singh; Raja Aadil Hussain Bhat (Aquaculture Nutrition, 2025)
Probiotics play a pivotal role in enhancing the health and growth of aquatic animals in aquaculture. These beneficial microorganisms contribute to improved digestion and nutrient absorption by producing digestive enzymes such as amylases, proteases, and lipases, besides providing essential nutrients. By creating a favorable microbial balance in the gastrointestinal tract (GIT), probiotics reduce harmful microorganisms and promote the proliferation of beneficial bacteria like Lactobacillus spp. and Bifidobacterium spp. This modification of gut microflora leads to more efficient digestion and significantly enhances overall health and growth performance in fish. Additionally, probiotics produce antimicrobial substances, such as bacteriocins and organic acids, which inhibit pathogenic bacteria and bolster disease resistance. They also play a crucial role in improving water quality in aquaculture systems by aiding in the turnover of organic nutrients and reducing toxic substances. Incorporating probiotics into aquaculture practices has demonstrated considerable potential in boosting the productivity and health of aquatic animals, making them an essential component of sustainable aquaculture. This review delves into the multifaceted benefits of probiotics, including enhanced feed utilization, immune responses, and pathogen resistance, and elucidates the mechanisms underlying these effects. Furthermore, it includes a bibliometric analysis of the past 30 years, providing a comprehensive overview of research trends and advancements in this field.